2019
DOI: 10.1080/24721735.2020.1819706
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of key issues in spa management: viewpoints from international industry professionals

Abstract: The aim of this paper is to examine the main issues that are pertinent to spa directors and employees when managing a spa. These include spa leadership; employee motivation; customer service; quality management; sustainability; health and safety; marketing and sales; financial management and funding; spa experience design; lifestyle and future trends. Using a sample of 45 in-depth e-interviews with respondents from 17 countries representing different positions within the spa sector, the authors analyse the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Incorporating features such as ambient music (Jeon et al , 2016), aromatherapy (Suess and Mody, 2017) and interactive service robots (Choi et al , 2020) can enhance the customer’s experience by creating a lasting and engaging impression. For instance, a spa that offers aromatherapy treatments, quiet music and low lighting might give visitors a relaxing and richly sensory experience (Smith and Wallace, 2019). Customers might feel more at ease and refreshed by indulging their senses through touch, scent and sound (Brochado et al , 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Incorporating features such as ambient music (Jeon et al , 2016), aromatherapy (Suess and Mody, 2017) and interactive service robots (Choi et al , 2020) can enhance the customer’s experience by creating a lasting and engaging impression. For instance, a spa that offers aromatherapy treatments, quiet music and low lighting might give visitors a relaxing and richly sensory experience (Smith and Wallace, 2019). Customers might feel more at ease and refreshed by indulging their senses through touch, scent and sound (Brochado et al , 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Smith et al, 2021., summarized literature about customer service in spas and highlighted the importance of quality of environment and facilities, staff attitude, as well as hygiene and cleanliness. Smith and Wallace's (2020) interviews with spa managers (many of whom were from the Balkan and V4 regions) also emphasized the need for staff training and for continual monitoring of quality. Strack and Raffay-Danyi's (2021) research in Hungary confirmed that cleanliness and staff were important aspects in customer satisfaction along with value for money and a quality experience.…”
Section: Literature Review Challengesmentioning
confidence: 99%
“…Digital tools enable spas to promote their services to younger guests as well as to monitor customer satisfaction through reviews and feedback (see e.g. Smith et al, 2020, who analyse customer satisfaction using TripAdvisor reviews of a Budapest spa). The challenge of recruiting and adequately remunerating well-trained staff depends very much on the salary structure in the given country and the availability of workers in a given region.…”
Section: Trendsmentioning
confidence: 99%
“…The transformation of medical spa resorts into wellness spa resorts for commercial and international tourists presents a serious challenge for European medical spa resorts, as they are still known for their healing and/or rehabilitation treatments and are visited mainly by national, non-commercial guests rather than international tourists. This seems to be a major challenge for many countries and there is an emerging body of research on the subject which pertains to European spas at the crossroads (Diekmann et al, 2020), the way the transition from medical to wellness spas has been managed in Slovenia (Lebe, 2014), the revitalisation of Serbian spas through wellness tourism (Dimitrovski & Todorović, 2015), the diversification of services at medical spa facilities to include wellness procedures in the Czech Republic (Kotikova & Schwartzhoffova, 2013), the changing functionality of Slovakian spas (Derco, 2017), the financial crises that have affected Slovakian spas as well as the role of wellness tourism (Derco & Pavlisinova, 2017), the profiles of commercial and non-commercial visitors in Polish spas (Dryglas & Różycki, 2017;Dryglas & Salamaga, 2017, and health tourism developments in Hungary (Smith et al, 2013;Smith & Wallace, 2019).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%